Analisis Kandungan Vitamin C dan β-Karoten Lada Katokon Toraja, Cabai Besar dan Cabai Keriting di Makassar - Sri Suhadiyah; Elis Tambaru; A. Masniawati (DEDIKASI, 2019)
Chili is one of the spices that are consumed by many Indonesians. It has several vitamins, one of which isvitamin C and ß-carotene is a pro-vitamin A which plays an important role in the formation of vitamin A. The studywas conducted in August 2018 and sampling from the regions Toraja and Malino. This study aims to determine thelevels of vitamin C in several types of chilli obtained by using iodine titration method and the levels of ß-caroteneby spectrophotometric method at a wavelength of 460-480 nm. The chili sample was first measuredmorphologically, weighed by base and dry weight and its water content. The test results showed vitamin C levels ofPepper Katokon Toraja Capsicum annuum L. Var. Sinensis is tested with seeds (0.129% / 10 g) and seedless(0.182% / 10 g). Large Chili Capsicum annuum L. Var. Abreviatum Fingerhuth was tested with seeds (0.220% / 10g) and seedless (0.223% / 10 g). Curly Chili Capsicum annuum L. Var. Longum sendt was tested with seeds(0.537% / 10 g) and seedless (0.592% / 10 g). Test results showed the levels of β-carotene Pepper Katokon TorajaCapsicum annuum L. Var. sinensis were tested with seeds (5.888mg / kg) and seedless (6.073mg / kg). Large ChiliCapsicum annuum L. Var. Abreviatum Fingerhuth was tested with seeds (5.529mg / kg) and seedless (6.338mg /kg). Curly Chili Capsicum annuum L. Var. Longum sendt was tested with seeds (6.655mg / kg) and seedless(6.942mg / kg). Conclusion The highest content of vitamin C and ß-carotene was found in Curly Chili Capsicumannuum L. Var. Longum sendt without seeds.